2015
DOI: 10.1007/s13277-015-4212-6
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effects of salinomycin on human ovarian cancer cell line (OVCAR-3)

Abstract: In this study, we studied the apoptotic and cytotoxic effects of salinomycin on human ovarian cancer cell line (OVCAR-3) as salinomycin is known as a selectively cancer stem cell killer agent. We used immortal human ovarian epithelial cell line (IHOEC) as control group. Ovarian cancer cells and ovarian epithelial cells were treated by different concentrations of salinomycin such as 0.1, 1, and 40 μM and incubated for 24, 48, and 72 h. Dimethylthiazol (MTT) cell viability assay was performed to determine cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…They also indicated that the cause of apoptosis is related to activation of death receptor 5 (DR5) pathway, which was observed even at low doses of SAL (0.5 µM) [56]. In contrast, the Kaplan group observed induction of apoptosis by upregulation of CASP3 in OVCAR3 cell line even at 0.1 µM of SAL [57].…”
Section: Discussionmentioning
confidence: 99%
“…They also indicated that the cause of apoptosis is related to activation of death receptor 5 (DR5) pathway, which was observed even at low doses of SAL (0.5 µM) [56]. In contrast, the Kaplan group observed induction of apoptosis by upregulation of CASP3 in OVCAR3 cell line even at 0.1 µM of SAL [57].…”
Section: Discussionmentioning
confidence: 99%
“…20 Studies by Kaplan and Teksen on the stable ovarian cancer cell line (OVCAR-3) demonstrated the activity of salinomycin: 40% of cells underwent apoptosis within 24 h of exposure. 21 A decrease was noted in the expression of the anti-apoptotic gene Bcl2.…”
Section: Salinomycinmentioning
confidence: 99%
“…45 Salinomycin also acted on OVCAR-3 human ovarian cancer cells through caspase-mediated apoptosis without harming normal cells. 46 Recently, salinomycin demonstrated anti-angiogenic activity by VEGFR2 signaling pathway in gastric cancer xenografts. 47 …”
Section: Salinomycin As An Anticancer Agentmentioning
confidence: 99%